Post-irradiation modulation of distribution of interacting vacancies in the elastically anisotropic b.c.c. crystals - Oliinyk, O.V.; Tatarenko, V.A. (Успехи физики металлов, 2018)
Spinodal mechanism of formation of a modulated structure in a spatial distribution of vacancies within the body-centred cubic (b.c.c.) crystal after irradiation is considered. The criterion of modulated-structure formation for the closed interacting-vacancies subsystem within the elastically anisotropic b.c.c. crystal is estimated. Розглянуто спинодальний механізм можливого формування надґратниці нанопор в об’ємно-центрованому кубічному (ОЦК) кристалі після опромінення. Проаналізовано критерій формування модульованої структури із взаємодійних вакансій у пружньо анізотропних ОЦК-кристалах. Оцінено залежність періоду модульованої структури розчину вакансій в ОЦК-Mo та ОЦК-Fe від температури. Рассмотрен спинодальний механизм возможного формирования сверхрешётки нанопор в объёмно-центрированном кубическом (ОЦК) кристалле после облучения. Проанализирован критерий формирования модулированной структуры из взаимодействующих вакансий в упруго анизотропных ОЦК-кристаллах. Оценена зависимость периода модулированной структуры раствора вакансий в ОЦК-Mo и ОЦК-Fe от температуры.